Student autonomy of feedback format in higher education and perceived functional behaviours for academic development - Abby Sparrow; Samantha Smith; Dominic Petronzi; Helen Wilson; Sarah Roeschlaub; Melanie Smith (Journal of Pedagogical Research, 2020)
In the current context of promoting active learning and raising student engagement within Higher Education, an increasing amount of research has looked at pedagogical-based design and factors that contribute to functional behaviours surrounding the interaction and use of academic assessment feedback. However, few studies have considered the perceived influence of student autonomy over feedback format and whether this promotes engagement and academic development. In this study, we recruited level 5 and 6 students (N=38 ) on an undergraduate Education Programme (that has consistently implemented student feedback choice) to participate in initial self-reporting and subsequent focus groups ('soft triangulation'). The findings revealed three core themes: [1] Personalisation - (a) sense of autonomy/involvement, (b) engagement and (c) motivation, [2] Clarity - (d) depth and detail, and [3] Areas for development. Overall, these findings suggest that feedback type - and the inherent option to choose - has a functional impact on academic engagement and development. We discuss these findings in relation to a sense of being valued that was associated with autonomy of choice, a divergence in how and when students engage with feedback, as well as the requirement for academic clarity and provision of formats that support academic development.